2021
DOI: 10.4269/ajtmh.20-1569
|View full text |Cite
|
Sign up to set email alerts
|

A Bead-Based Assay for the Detection of Antibodies against Trichinella spp. Infection in Humans

Abstract: Human trichinellosis can be diagnosed by a combination of medical history, clinical presentation, and laboratory findings, and through detection of anti–Trichinella IgG in the patient’s sera. ELISA using excretory–secretory (E/S) antigens of Trichinella spiralis larvae is currently the most used assay to detect Trichinella spp. antibodies. Bead-based assay can detect antibodies to multiple antigens concurrently; the ability to detect antibody to T. spiralis using a bead assay could be useful for diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Immunological techniques, e.g., ELISA, are the most common methods used to detect Trichinella antigens and their counterpart antibodies. Many parasitic proteins, for example, excretory-secretory (ES) antigens [ 21 , 22 ], serine protease [ 23 ], elastase-1 [ 24 ], and crude somatic antigen [ 25 ], have been used to develop diagnostic tests. Some studies found >90% sensitivity and specificity, unfortunately, barriers to the success of immunological techniques still exist.…”
Section: Introductionmentioning
confidence: 99%
“…Immunological techniques, e.g., ELISA, are the most common methods used to detect Trichinella antigens and their counterpart antibodies. Many parasitic proteins, for example, excretory-secretory (ES) antigens [ 21 , 22 ], serine protease [ 23 ], elastase-1 [ 24 ], and crude somatic antigen [ 25 ], have been used to develop diagnostic tests. Some studies found >90% sensitivity and specificity, unfortunately, barriers to the success of immunological techniques still exist.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of human Trichinellosis is mainly based on clinical symptoms and serological tests, such as ELISA, indirect immunofluorescence assay (IFA), enzyme immunohistochemistry technique (EIH), and Western-Blotting (WB), The International Commission on Trichinosis recommends ELISA, which detects anti-trichinella IgG in patients' serum by excretory secretion (E/S) antigen of Trichinella spiralis larvae. The sensitivity and specificity of total IgG were 93.6% and 94.3%, respectively [ 6 ]. The limitations of this method are that it has a high false-negative rate in the early stage of infection (1–3 months) and cannot distinguish between acute and previous infection [ 7 ].…”
Section: Discussionmentioning
confidence: 99%